2004
DOI: 10.1097/01.brs.0000141178.98157.8e
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Spinal Palpation for Diagnosis of Back and Neck Pain

Abstract: The quality of the research on interreliability and intrareliability of spinal palpatory diagnostic procedures needs to be improved. Pain provocation tests are most reliable. Soft tissue paraspinal palpatory diagnostic tests are not reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
5
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(181 citation statements)
references
References 51 publications
6
156
5
14
Order By: Relevance
“…Tests of joint-mobility are considered an important tool in physical therapy and manual therapy, but it seems difficult to obtain good inter-examiner agreement, most probably because the tests are based on palpation. The results of the tests for TMJ-mobility in the present study are slightly better than what have been reported on palpation tests for other joints/structures [22][23][24][25]. Robinson and co-workers (2009) found poor to moderate inter-tester reliability on palpation tests for identifying the spinous processes of C7 and L5.…”
Section: Functional Testscontrasting
confidence: 49%
See 1 more Smart Citation
“…Tests of joint-mobility are considered an important tool in physical therapy and manual therapy, but it seems difficult to obtain good inter-examiner agreement, most probably because the tests are based on palpation. The results of the tests for TMJ-mobility in the present study are slightly better than what have been reported on palpation tests for other joints/structures [22][23][24][25]. Robinson and co-workers (2009) found poor to moderate inter-tester reliability on palpation tests for identifying the spinous processes of C7 and L5.…”
Section: Functional Testscontrasting
confidence: 49%
“…Robinson and co-workers (2009) found poor to moderate inter-tester reliability on palpation tests for identifying the spinous processes of C7 and L5. The same group also found poor reliability for the joint-play test for the sacroiliac joint [23]. Generally, joint-mobility tests involving palpation seem to have lower reliability than pain provocation tests, and it has been hypothesized that this might depend on the experience and skills of the assessors [25,26].…”
Section: Functional Testsmentioning
confidence: 96%
“…Systematic reviews have previously addressed the reliability of some palpatory tests; [17][18][19] however, the studies within the systematic reviews are difficult to compare because of variations in testing technique and interpretation, as well as in the methodological approaches used. In our study, the values for k and k w showed unsatisfactory agreement, both within and between observers, for the palpatory test investigated.…”
Section: Discussionmentioning
confidence: 99%
“…83 The diagnostic reliability of many of the indicators of somatic dysfunction is poor. [84][85][86] Palpation of tenderness has acceptable inter-examiner reliability, but reliability for palpation of segmental motion restriction or tissue texture changes is generally poor. [84][85][86] The reliability for assessment of asymmetrical bony landmarks is fair to poor, 87 unless substantial asymmetry exists.…”
Section: Diagnostic Reliability and Validitymentioning
confidence: 99%